Development and Validation of a New Stability-indicating RP-HPLC Method for the Quantification of Etoricoxib in Tablets - Annapurna, Dr. Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Etoricoxib is also a bipyridine derivative used as a non-steroidal anti-inflammatory drug. A new stability-indicating reverse phase high-performance liquid chromatographic (HPLC) method has been developed for the quantification of Etoricoxib in tablet dosage forms. Materials and Methods: A Shimadzu HPLC system equipped Agilent C18 column was chosen for the chromatographic study with mobile phase formic acid:acetonitrile (52:48) and a flow rate of 0.8 mL/min (UV detection at 247 nm). Results and Discussion: Linearity was obeyed over the concentration range of 0.5–100 μg/mL with a linear regression equation y = 95013× – 11970 and a correlation coefficient of 0.9998. The limit of detection and limit of quantification were found to be 0.1557 and 0.4791 μg/mL, respectively. Stress degradation studies were performed, and the method was validated as per the International Council for Harmonisation guidelines. Conclusion: The RP-HPLC method so developed was found to be selective, specific, precise, accurate, robust, and useful for the estimation of Etoricoxib tablets.